Prevalence of Drug abuse among ante partum females, Obstetric Department, Beni Suef University Hospital, Egypt - Dalia Abd Elwhab Hassan1 , Manar .A Ahmad1 , Salwa Mahmoud Ali2 , Mohamed A Hussien2 ,Doaa M. Khalil (Institute of Medico-legal Publications Pvt Ltd, 2021)
The consumption of drugs of abuse among females in the Health Services is a frequent problem, but oftenit is not diagnosed. Aims: We have analyzed the variations in the clinical profile of female patients came toobstetric emergency department in a period of sex months and made screening for various drugs to assessthe percentage of addicted females in this period of life. Secondly, we have assessed also the accuracy of thepresumptive method of detection compared to the confirmatory method. Method: Urine samples were takenfrom pregnant females came to obstetric emergency department, Beni Suef University hospital and wasscreened to detect the drugs of abuse that taken by these females by immunoassay and GC- mass and clinicalassessment of the babies were done. Results: from 300 females there were 20 cases Tramadol positiveby immunoassay but all of them were false positive when GC-mass was used. There was a questionedcross reactivity between Ranitidine and tramadol by Immunoassay needing for more researches. 62.3% ofthe female were no educated 42% of the female’s husbands were SHISHA smokers. Intra uterine growthretardation was the most common fetal complicationConclusions: scientific survey which done to detect drug abuse among group of people should never dependon immunoassay methods. The belief that women are more biologically complicated than men and thatthey were too busy caring for their children to participate in studies should be changed. Women should beincluded in clinical researches.